“El Triunfo” Photovoltaic Power Plant; Rural Development Study - José Emilio Camejo Cuán; Rubén Ramos Heredia; Roger Proenza Yero (Borong Newinera Publisher, 2021)
The results of rural electrification in Cuba, from Photovoltaic Solar Energy, are presented as part of the technical-economic feasibility study of the use of medium-power Photovoltaic Plants in tropical climate conditions, based on the experiences obtained for more than 20 years of operation of the photovoltaic plant in the rural community